Ռազմական օմբուդսմենի ինստիտուտը զինված ուժերում. քաղաքացիական վերահսկողության ընթացակարգ - Ջիլավյան, Սվետլանա («ԱՐՑԱԽ» հրատ.)
Հոդվածում քննարկված է ռազմական օմբուդսմենի ինստիտուտի դերը զինված ուժերում քաղաքացիական վերահսկողության մեխանիզմի ձևավոր-ման մեջ։ Հեղինակը շեշտադրում է օմբուդսմենի կարևորությունը զինծառա-յողների իրավունքների պաշտպանության, ներքին բարեփոխումների խթանման և զինված ուժերում իրավական ու ժողովրդավարական վերահսկողության ամրապնդման հարցում։ Հետազոտության նպատակն է գնահատել Հայաստանի մարդու իրավունքների պաշտպանի գործող մոդելի արդյունավետությունը և քննարկել ռազմական օմբուդսմենի առանձին ինստիտուտի ներդրման նպատակահարմարությունը։ Հոդվածի հիմնական խնդիրներ են սահմանվել՝ ● ուսումնասիրել ռազմական օմբուդսմենի դերը զինծառայողների իրավունքների պաշտպանության և զինված ուժերում ժողովրդավարական վերահսկողության ամրապնդման գործում: ● Վերլուծել միջազգային փորձը և տարբեր երկրների օմբուդսմենի մոդելների առավելություններն ու թերությունները: ● Գնահատել Հայաստանի մարդու իրավունքների պաշտպանի ներկայիս գործառույթները և դրանց սահմանափակումները: ● Բացահայտել առանձին ռազմական օմբուդսմենի ինստիտուտի ստեղծման հնարավոր առավելություններն ու ռիսկերը: Հետազոտության մեթոդները ներառում են համեմատական վերլուծություն, միջազգային փորձի ուսումնասիրություն և Հայաստանի Հանրապետության օրենսդրական ու ինստիտուցիոնալ շրջանակի գնահատում: Կիրառվել են նաև որակական մեթոդներ՝ օմբուդսմենի մոդելների արդյունավետության և կիրառելիության գնահատման համար։ Հոդվածի եզրակացության մեջ առաջարկված է համապարփակ ուսումնասիրել ռազմական օմբուդսմենի ներդրման արդյունավետությունը Հայաստանում՝ համադրելով միջազգային փորձն ու ազգային առանձնահատկությունները։ The article examines the role of the military ombudsman institution in the formation of a civilian control mechanism in the armed forces. The author emphasizes the importance of the ombudsman's activities in protecting the rights of military personnel, promoting internal reforms, and strengthening legal and democratic control in the armed forces. The purpose of the study is to assess the effectiveness of the current model of the Human Rights Defender of Armenia and discuss the feasibility of introducing a separate military ombudsman institution. The main objectives of the article are: ● To study the role of the military ombudsman in protecting the rights of military personnel and strengthening democratic control in the armed forces. ● To analyze international experience, as well as the advantages and disadvantages of ombudsman models in different countries. ● To assess the current functions of the Human Rights Defender of Armenia and their limitations. ● To identify the potential benefits and risks of creating a separate institution of the military ombudsman. The research methods include comparative analysis, study of international experience, assessment of the legislative and institutional framework of the Republic of Armenia. Qualitative methods were also used to assess the effectiveness and applicability of ombudsman models. The article concludes with a comprehensive study of the effectiveness of introducing the military ombudsman institution in Armenia, combining international experience and national characteristics. 136 importance of the ombudsman's activities in protecting the rights of military personnel, promoting internal reforms, and strengthening legal and democratic control in the armed forces. The purpose of the study is to assess the effectiveness of the current model of the Human Rights Defender of Armenia and discuss the feasibility of introducing a separate military ombudsman institution. The main objectives of the article are: ● To study the role of the military ombudsman in protecting the rights of military personnel and strengthening democratic control in the armed forces. ● To analyze international experience, as well as the advantages and disadvantages of ombudsman models in different countries. ● To assess the current functions of the Human Rights Defender of Armenia and their limitations. ● To identify the potential benefits and risks of creating a separate institution of the military ombudsman. The research methods include comparative analysis, study of international experience, assessment of the legislative and institutional framework of the Republic of Armenia. Qualitative methods were also used to assess the effectiveness and applicability of ombudsman models. The article concludes with a comprehensive study of the effectiveness of introducing the military ombudsman institution in Armenia, combining international experience and national characteristics. Keywords: Human Rights Defender, civilian control, armed forces, legal restrictions, international experience, rights of military personnel, military ombudsman. В статье рассматривается роль института военного омбудсмена в формировании механизма гражданского контроля в вооруженных силах. Исследователь подчеркивает важность деятельности омбудсмена в защите прав военнослужащих, содействии внутренним реформам, усилении правового и демократического контроля в вооруженных силах. Целью исследования является оценка эффективности действующей модели Защитника прав человека Армении и обсуждение целесообразности введения отдельного института военного омбудсмена. Основными задачами статьи являются: ● изучить роли военного омбудсмена в защите прав военнослужащих и укреплении демократического контроля в вооруженных силах. ● проанализировать международный опыт, а также преимущества и недостатки моделей омбудсмена в разных странах. ● оценить текущие функции Защитника прав человека Армении и их ограничения. ● определить потенциальные преимущества и риски создания отдельного института военного омбудсмена. Методы исследования включают сравнительный анализ, изучение международного опыта, оценку законодательной и институциональной базы Республики Армения. Для оценки эффективности и применимости моделей омбудсмена также использовались качественные методы. В заключении статьи предлагается комплексное исследование эффективности введения института военного омбудсмена в Армении, сочетающее международный опыт и национальные особенности.
Keywords: Միջազգային հարաբերություններ